2014
DOI: 10.2478/ata-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Sunflower Achenes

Abstract: This work contains the results of measuring the electrical properties of sunflower achenes. The interest in electrical properties of biological materials resulted in engineering research in this field. The results of measurements are used for determining the moisture content, the surface level of liquid and grainy materials, for controlling the presence of pests in grain storage, for the quantitative determination of mechanical damage, in the application of dielectric heating, and in many other areas. Electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…capacitance ranges from 214.7 pF to 284.0 pF, dielectric constant from 4.63 to 6.17. The identical results for other biological materials were presented by other authors (Nelson et al, 2007;Novák, 2013;Novák and Vitázek, 2014) and thus it can be concluded that dielectric constant and loss tangent increased with an increase in material moisture content.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…capacitance ranges from 214.7 pF to 284.0 pF, dielectric constant from 4.63 to 6.17. The identical results for other biological materials were presented by other authors (Nelson et al, 2007;Novák, 2013;Novák and Vitázek, 2014) and thus it can be concluded that dielectric constant and loss tangent increased with an increase in material moisture content.…”
supporting
confidence: 87%
“…The principal drawbacks of the studied research are as follows: the absence of monitoring of energy processes occurring in the seed layer treated within the working chamber; absence of a closed-loop control system with feedback from monitored results; absence of automatic regulation of PEF parameters in accordance with the changes in the seed layer. The electrical characteristics of seeds are: layer capacitance, and seed dielectric constant, which are dependent on seed conditions (Nelson et al, 2007;Novák, 2013;Novák and Vitázek, 2014;Vitázek and Veres, 2013).…”
mentioning
confidence: 99%
“…A gap thickness between electrodes could range from 50mmup to100mm.The basic requirement to the installations was to create the electric field strength in the range of 4-20 kV•m -1 in the active zone. Hence, when designing, it is necessary to know some electrical parameters of seeds: dielectric constant, leakage resistance, dielectric loss tangent, and humidity being determined by the known methods [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Cultivated varieties and hybrids of sunflower are also characterized by a significant variation in plant height, which makes it difficult to cut and thresh exclusively the productive plant part, leading to the head loss, deterioration of the thresher and necessity to clean the combine. Due to sunflower characteristics, utilization of technical means for its harvesting is inevitably related to the crop losses and seed injury (Dalmis et al, 2013a;Dalmis et al, 2013b;Doronin, 2006;Fedorenko, 1985;Csanadi and Hamphoff, 2007;Gonulol et al, 2009;Miklič et al, 2012;Mirzabe and Chegini., 2015;Mirzabe et al, 2012;Novák and Vitázek,, 2014;Sekhon et al, 2004;Sudajan et al, 2002;Trubilin and Kravchenko, 2001).…”
Section: Vasiliy Dmitrievich Shaforostov Sergey Sergeevich Makarovmentioning
confidence: 99%